(untitled) (Journal of Engineering, 2008)
A series of laboratory tests were carried out on disturbed soil samples containing different gypsum contents. The soil samples were obtained from al-Jazeera south-west of Iraq. Tests were performed to obtain the physical and mechanical properties of the soil. In addition; permeability-leaching tests were conducted by using oedometer and large-scale Rowe cell apparatus to obtain the variation of the coefficient of permeability, dissolved gypsum and leaching strain with time. All samples were tested under similar conditions, e.g. the hydraulic gradient, vertical stress and leaching period. The soil samples designated N1, N2, and N3 are obtained from depths (0.5-0.75), (1.0-1.25), and (3.25-3.5) m and having gypsum content (31.43), (51.37), and (4.86) percentage respectively. Results of experimental work show that the coefficient of permeability, the percentages of dissolved gypsum and leaching strain measured from the oedometer test are higher than that measured from large-scale Rowe cell test for the same soil sample. The gypseous soil with higher gypsum content exhibited significant amount of leaching strain.